Problem Solving Abilities in Social Arithmetic of 8th Grade Students Reviewed From Cognitive Styles - Fuadi, Ukas Alif; Sujiwo, Dimas Andhita Cahyo; Anas, Aswar (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
Quality education in the SDGs aims to improve high-level thinking and problem-solving capabilities at all levels of education. Nevertheless at SMP Baitul Arqom, students has difficulties in solving mathematical problems, especially in social arithmetic. The aim of this research is to determine the ability of 8th grade students at SMP Baitul Arqom in solving social arithmetic problems in terms of impulsive and reflective cognitive styles. This research approach is descriptive, which describes the level of students' problem solving abilities based on impulsive and reflective cognitive styles. Then this research is a qualitative type, because the findings that will be explored in this research do not require procedural statistical analysis. This research was carried out at SMP Baitul Arqom Balung. Data sources include arithmetic test questions, MFFT, and interviews. The research subjects were class VIII students at SMP Baitul Arqom. Based on the results of the MFFT test and social arithmetic problem solving for 8th grade students at SMP Baitul Arqom, it shows that there were 9 impulsive students, 11 reflective students, and 4 students who were neither categorized as impulsive nor reflective. There is a clear difference between impulsive and reflective students. Impulsive students, IS1 and IS2, tended to be quick in responding but often inaccurate, indicating the need for practice in slowing down the decision-making process to increase accuracy. Meanwhile, reflective students, RS1 and RS2, were very accurate but slow, indicating the need for practice in speeding up the thinking process without sacrificing quality